Optimizing Supplier Selection for a Construction Project by a Cash-Flow Approach Using a Hybrid Metaheuristic Algorithm - Seyyed Esmaeil Najafi; Soheil Salahshour; Bijan Rahmani Parchikolaei (Big Data and Computing Visions)
Supplier selection is the practice of evaluating and selecting the best or most suitable supplier for the organization based on the candidates' qualities and qualifications. In large construction projects, supplier selection strongly impacts the quality of materials as well as the cash-flow and logistical support of the project. The issue becomes particularly important when a high number and volume of orders and a varied set of items are involved. If the procurement process is organized into several periods, the impact of Net Present Value (NPV) on the project's overall profit or loss becomes significant, as well. In this study, the solution to a multi-product multi-period supplier selection optimization problem is evaluated using a hybrid metaheuristic algorithm and considering the cash flow. Our analysis of the results shows that the algorithm is able to obtain the intended outcome within an appropriate timeframe and with high precision.